Referendum Design and Contingent Valuation: The NOAA Panel's No-Vote Recommendation - Carson, Richard T.; Hanemann, W. Michael; Kopp, Raymond J.; Krosnick, Jon A.; Mitchell, Robert Cameron; Presser, Stanley; Ruud, Paul A.; Smith, V. Kerry; Conaway, Michael; Martin, Kerry (The Review of Economics and Statistics, 1998)
This paper considers the effects for offering a “would-not-vote” option in contingent valuation (CV) questions framed using the referendum format. This approach arises from a suggestion made by the National Oceanic and Atmospheric Administration's (NOAA) panel on contingent valuation. The NOAA panel was asked to evaluate the use of this method for estimating the economic value of nonmarketed environmental resources in the context of natural resource damage assessments. This test used the CV questionnaire developed for the study of the Exxon Valdez oil spill conducted by the State of Alaska with in-person interviews. The findings suggest that when those selecting the “would-not-vote” response are treated as having voted “against” the program (a conservative coding), offering this option does not alter (1) the distribution of “for” and “against” responses (2) the estimates of willingness to pay derived from these choices, or (3) the construct validity of the results.